Avaliação do uso de serviços odontológicos ao longo da adolescência: um estudo de coorte quantitativo e qualitativo - Maroneze, Marília Cunha (2021)
Two studies will be presented in this thesis involving the subject use of dental services in adolescence. The first study aimed to assess which factors in early adolescence influence regular dental attendance in the end of adolescence, considering 6 years of follow up. The second study aimed to assess what was the prevalence of dental service use in the last year and to understand what are the barriers and facilitators in the use of the dental service by adolescents. A prospective cohort study started in 2012 with an epidemiological survey carried out in 20 schools located within the 5 administrative regions of Santa Maria. In total, 1134 adolescents with 12 years were evaluated in the baseline (T1). Data collection included clinical examinations and a structured questionnaire answered by the parents. Data were collected considering contextual, demographic, socioeconomic, behavioral and psychosocial conditions. The outcome of the first study, regular attendance, was evaluated using the self-reported of adolescents considering the reason for their last dental visit at follow up. We consider regular attenders as those who reported going to the dentist for dental checkup and non-regular attenders were adolescents who visit the dentist due oral problems. Multilevel Logistic Regression models were performed to evaluate the association between baseline variables and routine dental attendance. A total of 759 adolescents were revaluated at T2. Having untreated dental caries (OR=0.66, 95% CI=0.47, 0.93) and malocclusion (OR=0.65, 95% CI=0.46, 0.90) were significantly associated with no routine regular attendance during follow up. A sequential explanatory mixed‐methods design was performed in the second study. In the quantitative phase, the prevalence of adolescents‘ dental visit in the last year was evaluated. Semi‐structured interviews were conducted consecutively in adolescents‘ residences in qualitative phase. All interviews were audio‐recorded until saturation was reached and analyzed according to thematic analysis proposed by Braun and Clarke. The prevalence of dental visit in the last year was 71.8%. From the 13 interviews conducted three subcategories emerged from the theme barriers to dental service: priorities and interests, difficulty of access, delay and difficult to get consultation. The subcategories that emerged from the facilitators were: motivation and health professionals at school. Then, dental caries and malocclusion have a negative influence on regular dental attendance. Furthermore, the majority of adolescents only visit the dentist due curative problems. Adolescents express the desire to have dentist and other health professionals inserted in school. This monitoring must be carried out in the beginning of adolescence due to the behavioral changes that occur in this period, which can contribute to oral problems. In this sense, we highlight the importance of longitudinal intersectional actions carried out between the health and education sectors to promote oral health among adolescents.